The Integration of Sustainability Accounting and ESG Reporting in Enhancing Corporate Transparency and Accountability in the Era of Sustainable Economy - Eko Cahyo Mayndarto; Ayke Nuraliati; Nada Cantika Putri Kadua (Dhana, 2026)
The growing emphasis on sustainability and Environmental, Social, and Governance (ESG) principles has transformed modern corporate governance by demanding higher levels of transparency and accountability in corporate reporting practices. Companies are increasingly required to disclose not only financial performance but also environmental and social impacts through sustainability accounting and ESG reporting frameworks. This study aims to analyze the integration of sustainability accounting and ESG reporting in enhancing corporate transparency and accountability in the era of a sustainable economy. The research adopts a quantitative approach using secondary data collected from corporate annual reports, sustainability reports, and ESG disclosures of companies that consistently publish sustainability information. Data analysis was conducted using descriptive statistics and multiple regression analysis to examine the relationship between sustainability accounting, ESG reporting, corporate transparency, and corporate accountability. The results indicate that sustainability accounting disclosure and ESG reporting have a positive and statistically significant influence on corporate transparency and accountability. Companies that integrate sustainability accounting practices with structured ESG reporting frameworks tend to provide more comprehensive, reliable, and comparable sustainability information. These disclosures strengthen investor confidence, support risk management, and enhance corporate governance effectiveness. The study concludes that the integration of sustainability accounting and ESG reporting is essential for improving the credibility of sustainability disclosures and for strengthening transparency and accountability within corporate governance systems in the era of sustainable economic development.